Potential application of Aloe vera gel in edible packaging development - Đoàn Thị Quỳnh Hoa; Trương Kim Phượng; Nguyễn Minh Xuân Hồng (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kỹ thuật và Công nghệ)
Edible packaging is an effective solution for preserving and enhancing the value of food products. Edible packaging with good biodegradability is also receiving attention regarding sustainable and environmentally friendly production and consumption trends. As a medicinal plant commonly grown worldwide and in Vietnam, aloe vera is a potential material that has been researched and applied in food preservation. Aloe vera film has been proven to have the ability to prolong the shelf-life, reduce oxidation, resist harmful microorganisms and fungi, and maintain the sensory values of the food product. This article aims to provide information on aloe vera gel’s properties and potential applications in edible packaging.